2007
DOI: 10.1111/j.1365-2567.2006.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Local thermal injury elicits immediate dynamic behavioural responses by corneal Langerhans cells

Abstract: Summary Langerhans cells (LCs) represent a special subset of immature dendritic cells (DCs) that reside in epithelial tissues at the environmental interfaces. Although dynamic interactions of mature DCs with T cells have been visualized in lymph nodes, the cellular behaviours linked with the surveillance of tissues for pathogenic signals, an important function of immature DCs, remain unknown. To visualize LCs in situ, bone marrow cells from C57BL/6 mice expressing the enhanced green fluorescent protein (EGFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…Sun et al (2006) demonstrated that IL-1 receptor antagonist prevented apoptosis during ex vivo expansion of human limbal epithelial cells cultivated on human amniotic membranes. Ward et al (2007) found that IL-1 receptor antagonist modulated immediate dynamic behavioral responses by corneal Langerhans cells in response to corneal thermal injury.…”
Section: Discussionmentioning
confidence: 95%
“…Sun et al (2006) demonstrated that IL-1 receptor antagonist prevented apoptosis during ex vivo expansion of human limbal epithelial cells cultivated on human amniotic membranes. Ward et al (2007) found that IL-1 receptor antagonist modulated immediate dynamic behavioral responses by corneal Langerhans cells in response to corneal thermal injury.…”
Section: Discussionmentioning
confidence: 95%
“…It is not clear from these studies whether the cells are migrating to the infection site, or from the site of infection in transit to the lymphatics. However, it has been reported that corneal Langerhans cells laterally migrate to a local thermal injury (45). Additionally, increased numbers of DC have been detected in the dermis at the border of human burn wounds (46).…”
Section: Figurementioning
confidence: 97%
“…There are a number of possible explanations for the presence of these long nonbridged nanotubes. They may indeed be forming a connection to a neighboring but undetected cell or their processes could be seeking contact with distantly located cells in a manner akin to the recently described "dendrite surveillance extension and recycling habitude" (dSEARCH) behavior of DCs (23,24). De novo nanotubes, yet to establish a connection to neighboring cells, have been described in culture conditions (1,19).…”
Section: F-actin Staining Of Membrane Nanotubesmentioning
confidence: 99%